Propuesta didáctica para el aprovechamiento educativo de la visita a un parque temático y generar actitudes positivas hacia el aprendizaje de las ciencias - Londoño Villamil, Germán; Solbes Matarredona, Jordi; León Urquijo, Ana Patricia (Revista Científica, 2011)
This article presents teaching strategies used teachers of secondary the College Santa Teresa of Jesus of the municipality of Armenia, training national culture agricultural Panaca before, during and after visits with different groups of students of secondary education and vocational average Park use science to generate positive towards natural sciences learning attitudes. Preinstruccionals teaching strategies are presented in the formal environment: two pre-test of attitudes (care for the environment and farming), the relevant items of the pre-test goals. Coinstruccionals in the non-formal atmosphere where students observed, didactic strategies collected information directly in the visit and processed information in the formal atmosphere of the classroom class. Postinstruccional formal atmosphere and non-formal, comparison of results and the application of the post-test of attitudes didactic strategies. Finally experience results and conclusions.